Pengembangan LKPD (Lembar Kerja Peserta Dididk) Praktikum Berbasis Inkuiri Terbimbing pada Materi Asam Basa - Ekon; Fahyuddin; Abraham Rahman (Sains: Jurnal Kimia dan Pendidikan Kimia, 2023)
This research aims is Developing Guided Inquiry-based practicum LKDP which was developed on valid acid-base material and Testing the implementation of guided inquiry-based practicum LKDP which was developed on acid-base material. The subjects in this research were class XI MIA4 students at SMA Negeri 1 Lawa totaling 30 students. Subjects were taken using purposive sampling, namely determining samples with certain considerations that were deemed able to provide maximum data. The instrument used to measure the implementation of guided inquiry-based practical LKPD is a response questionnaire (teacher and student). The results of data analysis show that 1) The validity of the guided inquiry-based practicum LKDP from the validation results of 2 validators shows that media validators have an average assessment presentation of 88.57% with very feasible criteria and material validators have an average assessment percentage of 90.90 If the criteria are very feasible, then the LKPD is worth testing. 2) The implementation of the guided inquiry-based practical LKPD in small groups obtained a percentage of students who strongly agreed 88.88%, while for large groups the percentage of students who strongly agreed was 91.93% and for the teacher percentage the percentage value was 88%.